2013
DOI: 10.21608/jssae.2013.52494
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Wheat Yield Under N, K and B Fertilization

Abstract: Two field experiments were conducted at Sakha Agricultural Research Station, North Delta, Egypt during two successive growing seasons (2010-2011 and 2011-2012) to study the effect of nitrogen fertilization with and without K and B application on wheat yield in addition to evaluate quantitatively the response of wheat grain yield to fertilizer application using a polynomial quadratic equation. Five N levels (0, 30, 60, 90, and 120 kg N fed-1) were applied as a main plots, with 2 levels of K (0 and 50 kg K2O fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…It can be concluded that the increasing amount of nitrogen fertilizer, consequently get higher grain yield. These results are in conformity with El-Gizawy ( 2005); Mosaad et al, (2013) and Gazia and Abd EL Aziz (2013).…”
Section: -Grain Yieldsupporting
confidence: 92%
See 1 more Smart Citation
“…It can be concluded that the increasing amount of nitrogen fertilizer, consequently get higher grain yield. These results are in conformity with El-Gizawy ( 2005); Mosaad et al, (2013) and Gazia and Abd EL Aziz (2013).…”
Section: -Grain Yieldsupporting
confidence: 92%
“…Soil fertility continues to decline because of combined effects of increasing pressure for land use for crop production, inadequate compensation of nutrients exported and lack of nutrients management. Gazia and Abd EL Aziz (2013) concluded that increasing N level up to 90 kg fed -1 led to a significant increase in wheat grain yield. Mosaad et al, (2013) showed that wheat grain and straw yields and N-uptake by grain and straw increased with use of mineral fertilizer rates up to 90 kg N fed -1 , but N utilization efficiency for wheat crop was decreased.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the increasing amount of nitrogen fertilizer consequently results in higher grain yield. These results are in conformity with El-Gizawy (2005) [6] ; Mosaad et al, (2013) [21] and Gazia and Abd EL Aziz (2013) [7] . Data pertaining to fig.…”
Section: Grain Yield (Q/ha)supporting
confidence: 91%